2022
DOI: 10.1126/science.abn1593
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary network of whiptail lizards reveals predictable outcomes of hybridization

Abstract: Hybridization between diverging lineages is associated with the generation and loss of species diversity, introgression, adaptation, and changes in reproductive mode, but it is unknown when and why it results in these divergent outcomes. We estimate a comprehensive evolutionary network for the largest group of unisexual vertebrates and use it to understand the evolutionary outcomes of hybridization. Our results show that rates of introgression between species decrease with time since divergence and suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…Phylogenomic data have the potential to be very complex, both in clades that are well-understood to be recalcitrant like Andean plant radiations (Pease et al 2016; Vargas et al 2017), and increasingly in less expected systems like lizards (Barley et al 2022). To best address this complexity, we advocate for the observation of empirical phylogenomic data, including gene tree alignments and topologies, and that data curation be tailored to unique properties of individual datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenomic data have the potential to be very complex, both in clades that are well-understood to be recalcitrant like Andean plant radiations (Pease et al 2016; Vargas et al 2017), and increasingly in less expected systems like lizards (Barley et al 2022). To best address this complexity, we advocate for the observation of empirical phylogenomic data, including gene tree alignments and topologies, and that data curation be tailored to unique properties of individual datasets.…”
Section: Discussionmentioning
confidence: 99%
“…However, these same distance-dependent mechanisms also reduce the overall number of gene flow events, potentially mitigating the effects of increased locality. Ultimately, if systems with distance-dependent gene flow ( e.g ., Chapman and Burke, 2007; Tea et al, 2020; Barley et al, 2022) have an abundance of events, it may pose challenges to methods that make certain topological assumptions of the underlying phylogenetic network.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, if systems with distance-dependent gene flow (e.g., Chapman and Burke, 2007;Tea et al, 2020;Barley et al, 2022) have an abundance of events, it may pose challenges to methods that make certain topological assumptions of the underlying phylogenetic network.…”
Section: Topological Properties Of Phylogenetic Networkmentioning
confidence: 99%
“…This work has shown that the likelihood of behavioural interference decreases with increasing divergence time (e.g. Drury et al ., 2020; Barley et al ., 2022) likely owing to relative similarity in the perceptual systems and agonistic and/or mating signals used in closely related species (Grether et al ., 2009; Orians & Willson, 1964). Consequently, behavioural interference is thought to have a strong impact on the rate of speciation by limiting the rate at which two recently diverged allopatric lineages can coexist in secondary sympatry (Tobias et al ., 2020).…”
Section: Future Directionsmentioning
confidence: 99%